MATHEMATICAL MODELING OF HUMAN PHYSIOLOGICAL PROCESSES AS A TOOL FOR DISEASE DIAGNOSIS AND PROGNOSIS (World Bulletin of Education and Learning, 2025)
The article explores the application of mathematical modeling in understanding, diagnosing, and predicting human physiological processes. It highlights how mathematical equations and computational models serve as fundamental tools in analyzing the dynamics of vital systems such as cardiovascular, respiratory, metabolic, and thermoregulatory functions. Through mathematical abstraction, these models make it possible to simulate complex biological interactions, predict disease development, and test medical hypotheses without invasive experimentation. The study emphasizes the interdisciplinary nature of mathematical modeling, combining knowledge from mathematics, medicine, physics, and computer science to form an integrated approach toward health research. It also discusses the potential of such models for early detection of abnormalities, optimization of treatment strategies, and development of personalized healthcare systems. For the pedagogical context, mathematical modeling is presented as a means of enhancing analytical and problem-solving skills among students of mathematical and medical disciplines, promoting critical thinking and interdisciplinary competence.
Keywords: Mathematical modeling, physiology, disease prognosis, computational biology, medical diagnostics, biostatistics, interdisciplinary education, simulation, biomedical engineering, quantitative analysis.